isomiR2Function: An Integrated Workflow for Identifying MicroRNA Variants in Plants - Yang, Kun; Sablok, Gaurav; Qiao, Guang; Nie, Qiong; Wen, Xiaopeng (Frontiers in Plant Science, 2017)
In plants, post transcriptional regulation by non-coding RNAs (ncRNAs), in particular miRNAs (19-24 nt) has been involved in modulating the transcriptional landscape in developmental, biotic and abiotic interactions. In past few years, considerable focus has been leveraged on delineating and deciphering the role of miRNAs and their canonical isomiRs in plants. However, proper classification and accurate prediction of plant isomiRs taking into account the relative features by which we define isomiRs, such as templated or non-templated is still lacking. In the present research, we present isomiR2Function, a standalone easily deployable tool that allows for the robust and high-throughput discovery of template and non-templated isomiRs. Additionally, isomiR2Function allows for identification of differentially expressed isomiRs and in parallel target prediction based on both transcripts or PARE-Seq either using Targetfinder or Cleaveland. isomiR2Function allows for the functional enrichment of the detected targets using TopGO package. Benchmarking of isomiR2Function revealed highly accurate prediction and classification of isomiRs as compared to the previously developed isomiR prediction tools. Additionally, the downstream implementation of additional features allows isomiR2Function to be classified as a single standalone tool for isomiR profiling from discovery to functional roles. All in all, isomiR2Function allows the streamline processing of the miRNA-seq for the identification and characterization of isomiRs with minimal efforts. isomiR2Function can be accessed through: https://github.com/347033139/ isomiR2Function